2014
DOI: 10.3390/nu6041618
|View full text |Cite
|
Sign up to set email alerts
|

Selected Activities of Citrus Maxima Merr. Fruits on Human Endothelial Cells: Enhancing Cell Migration and Delaying Cellular Aging

Abstract: Endothelial injury and damage as well as accumulated reactive oxygen species (ROS) in aging play a significant role in the development of cardiovascular disease (CVD). Recent studies show an association of high citrus fruit intake with a lower risk of CVD and stroke but the mechanisms involved are not fully understood. This study investigated the effects of pummelo (Citrus maxima Merr. var. Tubtim Siam, CM) fruit extract on human umbilical vein endothelial cell (HUVECs) migration and aging. The freeze-dried po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 43 publications
0
20
1
2
Order By: Relevance
“…Numerous studies have shown that replicative senescence can be viewed as a result of a constant moderate stress such as stimuli from reactive oxygen species (ROS) to the cells [22]. Continuous cultivation of HUVEC cells could promote endogenous formation of ROS [23,24]. In this study, we observed gradually decreased levels of several antioxidant molecules (glutathione, creatine and fumarate).…”
Section: Promoted Oxidative Stress During Cellular Replicative Senescmentioning
confidence: 53%
“…Numerous studies have shown that replicative senescence can be viewed as a result of a constant moderate stress such as stimuli from reactive oxygen species (ROS) to the cells [22]. Continuous cultivation of HUVEC cells could promote endogenous formation of ROS [23,24]. In this study, we observed gradually decreased levels of several antioxidant molecules (glutathione, creatine and fumarate).…”
Section: Promoted Oxidative Stress During Cellular Replicative Senescmentioning
confidence: 53%
“…Cellular senescence is a major cause of aging. It is characterized by numerous biochemical changes, such as the increased activity of β-galactosidase [ 25 ]. It is well known that the exposure of H 2 O 2 induces higher β-galactosidase activity that allows an in vitro identification of senescent cells [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context and in the framework of the ageing process, citrus crops are one of the most important in the world, as producers of high vitamin C and polyphenolic content, and the fruits are among the most valuable functional diets, highly consumed globally in the form of fresh as well as processed juices and shown to lower oxidative stress-related diseases and ageing [6]. Furthermore, an extract of pummelo ( Citrus maxima ) was able to attenuate increased ROS levels in aged cells [7], while epidemiological studies reveal a strong correlation between high levels of citrus fruit consumption and low incidence of age-related diseases such as cardiovascular diseases and cancer [8]. Besides, citrus fruits showed cytoprotective action which is enhanced by the presence of antioxidants including vitamin C and flavonoids [9].…”
Section: Introductionmentioning
confidence: 99%